Imagined Communities and Identities in English as a Foreign Language (EFL) Learning: A Literature Review - Luong, Vu Anh; Tran, Thao Quoc (JET ADI BUANA, 2021)
Imagined community and identity have been recognized as critical aspects in English language learning. Imagined community refers to the ideal community that learners wish to get engaged in, while imagined identity refers to the ideal self that language learners wish to become in the future. However, there is a scant research on these two notions in relation to English as a foreign language (EFL) learning. To that end, this paper aims to present the literature review of the contemporary theories on imagined communities and identities in EFL learning. It first discusses the imagined communities regarding the functions, community of practice, notions of imagined communities and concepts of imagined EFL classroom communities. It then scrutinizes imagined identities in terms of poststructuralists’ theory, English language learners’ identities, notion of imagined identity and EFL learners’ imagined identity. This paper is hoped to provide a timely and needed conceptual framework for other relevant constructs (e.g., English language learning investment) in English language learning.